Potential of a Palm Oil-Based Surfactant in Nanoemulsion Formulation for Botanical Insecticide Piper aduncum - Lina, Eka Candra; Rusli, Rusdi; Fadhlurrahman, Rayhan; Rustam, Rusli; Nelly, Novri; Yanti, Rina Novia (AGRIVITA Journal of Agricultural Science, 2025)
Palm oil-based surfactants have the potential to be used as botanical insecticide formulations that are environmental friendly. This study was aimed to obtain information on the potential of palm oil-based surfactants as substitutes of synthetic surfactants in the preparation of botanical insecticide formulations to control Spodoptera frugiperda in organic farming. The experiment consisted of two stages, namely the stability test (surfactant and formulation) and the second stages were to test the insecticidal activity of the formulation against the targeted insects. The method of stability tests was following the standards of Collaborative International Pesticides Analytical Council (CIPAC). The insecticidal activity test used the leaf immersion method with the observation parameters of larval mortality and larval development time. The relationship between treatments and larval mortality was analyzed using probit to determine the LC50 and LC95 values. The data obtained were analyzed for variance and continued with the Least Significant Different test at 5% level. This study showed that palm oil has potential as a surfactant in the Piper aduncum nanoemulsion formulation according to CIPAC standards and affected the mortality of S. frugiperda with LC50 concentration of 0.55 and LC95 of 2.95.